Cash Flow vs. Digital Flow: The Role of Online Sales in Maintaining MSME Financial Stability - Hari Sriwijayanti; Shinta Bella; Nike Apriyanti (Journal of Management and Social Sciences, 2026)
This study aims to analyze the role of online sales in maintaining the financial stability of Micro, Small, and Medium Enterprises (MSMEs) in West Sumatra, Indonesia. The increasing adoption of digital channels, such as marketplaces, social media, messaging applications, live selling, and digital payment systems, has transformed online sales into not only marketing tools but also mechanisms that may affect cash flow continuity and business sustainability. Despite their growing importance, empirical evidence regarding the contribution of online sales to MSME financial stability remains limited. This study employs a quantitative explanatory research design. The population consists of MSME owners in West Sumatra who utilize online sales, while purposive sampling was used to select respondents who had engaged in online selling for at least one year and maintained cash flow records. Data were collected from 102 respondents through a structured questionnaire using a five-point Likert scale and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings reveal that online sales have a positive and significant effect on financial stability, with a path coefficient of 0.632, a t-value of 9.214, and a p-value below 0.001. These results indicate that effective use of online sales enhances cash flow continuity, income regularity, working capital adequacy, and financial resilience. However, the benefits depend on disciplined management of digital costs, discounts, platform fees, shipping expenses, product returns, and cash flow records. This study contributes to MSME digitalization literature by highlighting online sales as a strategic instrument for strengthening financial stability rather than merely a marketing channel.